2011
DOI: 10.1128/jb.00288-10
|View full text |Cite
|
Sign up to set email alerts
|

ThetibAdherence Locus of EnterotoxigenicEscherichia coliIs Regulated by Cyclic AMP Receptor Protein

Abstract: Enterotoxigenic Escherichia coli (ETEC) is a Gram-negative enteric pathogen that causes profuse watery diarrhea through the elaboration of heat-labile and/or heat-stable toxins. Virulence is also dependent upon the expression of adhesive pili and afimbrial adhesins that allow the pathogen to adhere to the intestinal epithelium or mucosa. Both types of enterotoxins are regulated at the level of transcription by cyclic AMP (cAMP) receptor protein (CRP). To further our understanding of virulence gene regulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…However, the studies do appear to affirm a central role of cAMP and the cAMP receptor protein (CRP) in modulation (41) of known (22) and putative (42) virulence genes, including genes involved in flagellar biosynthesis (7), whose expression is known to be under the control of crp (43). Interestingly, the crp gene is itself negatively autoregulated by the cAMP-CRP complex (44).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the studies do appear to affirm a central role of cAMP and the cAMP receptor protein (CRP) in modulation (41) of known (22) and putative (42) virulence genes, including genes involved in flagellar biosynthesis (7), whose expression is known to be under the control of crp (43). Interestingly, the crp gene is itself negatively autoregulated by the cAMP-CRP complex (44).…”
Section: Figmentioning
confidence: 99%
“…To construct transcriptional reporter fusions, regions upstream of the gene of interest were amplified by PCR and cloned into pHKLac1, a promoterless lacZYA reporter plasmid (22) containing an R6K␥ origin of replication and HK022 phage attP site for integration into the respective HK022 chromosomal attB site (23). Briefly, a 935-bp amplicon containing the eaeH promoter region (from Ϫ594 to ϩ341 of eaeH) was PCR-amplified using primers jf032812.1 (5=-GATCGGATCCGATCCCATAGTTTATCCGG-3=) and jf032812.2 (5=-GATCGAATTCTTCCCGAGCCACTCCTG-3=) and directionally cloned into the corresponding BamHI and EcoRI sites (respectively underlined in sequences listed above) of pHKLac1, resulting in plasmid pQL002.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…To date, the majority of the ETEC transcriptional studies have focused on the ETEC rns regulon (11), which has largely been associated with the regulation of CF expression (3,9,23), although binding motifs have been identified adjacent to other genes (44). No regulator has been identified that is associated with the expression of the enterotoxins.…”
mentioning
confidence: 99%
“…16 We're Here! Coincident with these events, genes governing the metabolism of key signaling molecules including the AI-2 autoinducer and c-di-GMP, as well as crp encoding the cAMP receptor protein (CRP), a major regulator of essential virulence traits, 17,18 are significantly modulated as bacteria move from planktonic to adherent populations. Although the precise impact of these signals on the expression of ETEC virulence genes is still being determined, the major changes in surface architecture of these pathogens upon interaction with intestinal cells clearly suggest that these organisms are programmed to respond to their environment in an orchestrated fashion that involves the modulation of both pathovar-specific genes like etpA and those genes encoding highly conserved features such as type 1 fimbriae.…”
Section: Challenges and Opportunities Moving Forwardmentioning
confidence: 99%